Fertility and pregnancy outcomes in women with nonclassic 21‐hydroxylase deficiency. (17th November 2022) - Carrière, Camille; Nguyen, Lee S.; Courtillot, Carine; Tejedor, Isabelle; Chakhtoura, Zeina; Bellanné‐Chantelot, Christine; Tardy, Véronique; Leban, Monique; Touraine, Philippe; Bachelot, Anne
Abstract: Introduction: Overall fertility and pregnancy outcomes in patients with nonclassic congenital adrenal hyperplasia (NCCAH) have been poorly studied. It has been suggested that hydrocortisone (HC) may decrease the time to conceive (TTC) and the rate of miscarriage in these patients. Objectives: To describe fertility and pregnancy outcomes in a large cohort of NCCAH women. The secondary objective was to identify factors that could impact reproductive outcomes, with a particular focus on HC dose and genetic status. Design: Retrospective study in a referral center for congenital adrenal hyperplasia. Patients and Measurements: One hundred seventy‐three female patients with NCCAH confirmed by genetic testing, followed in our center between 2010 and 2019. Results: Among the 173 patients, 95 women had a parental project, 86 of whom presented 176 pregnancies, 56% under glucocorticoid (GC) treatment and 44% without, and 76 women obtained 128 live births. Two‐thirds of the patients regularized their cycle under GC treatment, with significant decrease of androgens and progesterone levels. This treatment was associated with a shortening of TTC (coef β = −.196, information coefficient [IC] = [−10.7; −0.91], p = .021). Androgen levels and TTC were positively correlated to the rate of miscarriage (OR = 4.8, IC = [1.15; 20.34], p = .021 for testosterone, OR = 1.4, IC = [1.05; 1.81], p = .02 for androstenedione, and OR = 1.03, IC = [1.01; 1.06], p = .015 for TTC). There was no difference in terms of obstetric outcomes between patients with or without GC treatment. CYP21A2 genotype had no impact on pregnancy outcome or TTC. Conclusions: Infertility is relative in patients with NCCAH. HC seems beneficial for fertility and pregnancy outcomes, especially for patients with menstrual disorders and high preconceptional androgen levels.